The female and male mitochondrial genomes of Unio delphinus and the phylogeny of freshwater mussels (Bivalvia: Unionida). Issue 1 (1st January 2016) - Fonseca, Miguel M.; Lopes-Lima, Manuel; Eackles, Michael S.; King, Tim L.; Froufe, Elsa
Abstract: We have sequenced the female and male mtDNA of Unio delphinus and inferred the Unionidae phylogeny using 41 complete mtDNA sequences. Additionally, we compared the concatenated mtDNA trees with those using single or combination of two mtDNA genes to identify the best genes to use in the absence of complete mitogenomes. The gender-specific mtDNAs of U. delphinus contain all Unionida mtDNA specific features. The mtDNA phylogeny supports the reciprocal monophyly of the gender-specific clades but it was inconclusive regarding Unionidae subfamilies relationships. The gene trees topologies using ND5 or 16S-rRNA with ND1 were the closest trees to the mtDNA trees.